Sosialisasi Model Pembelajaran Problem Based Learning Berbantuan Media Buku Digital Flipbook pada Guru SMA Negeri 4 Balikpapan untuk Meningkatkan Keterampilan Membaca Peserta Didik - Maryatin Maryatin; Ananda Intan Rahmadani; Rahma Devitaningrum; Mirnawati Besip; Nova Sri Murdaya; Rita Manullang (Abdimas Universal, 2024)
The students' reading skills at SMA Negeri 4 Balikpapan need to be improved because there are still students who get low scores. The purpose of this activity is to introduce to teachers about Problem Based Learning (PBL) learning model assisted by flipbook media to improve students' novel text reading skill at SMA Negeri 4 Balikpapan. The socialization was attended by Indonesian language teachers. After the training ended, the implementation of problem-based learning model assisted by flipbook media was conducted in one of the classes. Learning activities with PBL model assisted by flipbook media were conducted in several meetings with the method used, namely cycle I and II consisting of planning, implementation, observation, and reflection. Data collection techniques using tests, distributing questionnaires, and documentation. The result of implementation shows that the application of problem based learning model effectively improves the reading skill of students of class XII IPS 2 SMA Negeri 4 Balikpapan in Indonesian language subject of novel material by 10.98%. It can be concluded that the implementation of problem based learning model assisted by flipbook can improve the reading skill of students of class XII IPS 2 at SMA Negeri 4 Balikpapan.